New insight into the molecular phylogeny and morphometrics of the genus Acer L. (Sapindaceae) native to Turkey - ACAR, Pelin; Seki, Nagihan; Bani, Barış; Demircioğlu, Nurcan; DUMAN, Hayri; Kaya, Zeki (Wiley, 2024)
This study investigates the phylogenetic relationships, taxonomic status, and morphometric analysis of 21 naturally occurring taxa of the Acer genus in Turkey. A comparative analysis was conducted using 18 informative morphometric characters and DNA sequence data from the cpDNA ndhF, trnL-F, and nrDNA ITS gene regions. To date, there has been no comprehensive molecular and morphometric study conducted on the genus in Turkey. Factor Analysis of Mixed Data (FAMD) was performed on selected morphometric traits, revealing highly distinctive characteristics for the Acer genus at the series, sectional, species, and sub-species levels, including Dim1 traits such as leaf length, leaf width, petiole length, loculus length, loculus width, fruit wing length, and fruit length, as well as Dim2 traits such as pubescence of leaf beneath, margin, latex, and form of nutlets, along with inflorescence, bud, and shoot features. The nuclear ITS and chloroplast trnL-F gene regions also exhibited significant diversity and provided valuable information. Phylogenetically, Acer species in Turkey showed close relationships with species native to the Eurosiberian phytogeography. The results of the phylogenetic and morphometric analyses offered reliable taxonomic clarifications for the first time, specifically for the species Acer tauricolum, A. divergens (endemic to Turkey), A. orthocampestre, and A. cappadocicum subsp. cappadocicum. The chloroplast lineage of Acer species native to Turkey appears to have originated in the late Oligocene and experienced significant diversification during the Miocene. The majority of Acer phylogenetic positions in Turkey are likely influenced by the habitats created by the northern mountain ranges.
Keywords: 15. Life on land